Wind and wind driven-rain characteristics in Singapore - Choi, Edmund Cheong Chuen. (2008)
This study investigates the unobstructed wind-driven rain over an open field. It looks into three important areas of WDR, intensity-duration relationship, driving rain intensity coefficient and raindrop size distribution (DSD).